Comparative Analysis of Different Heliostat Field Control Algorithms - Andonov, Ivan; Ojleska Latkoska, Vesna; Stankovski, Mile (Society for Electronics, Telecommunications, Automatics and Informatics of the Republic of Macedonia - ETAI, 2021)
This study presents the use of various algorithms for control of a field of heliostats, through which a thermal power plant with concentrated solar energy is controlled. The design of the control algorithms consists of several steps. First, in order to obtain the mathematical model of the system, the real system is identified according to the gray box and the least-square method. The data used to identify the system is generated by step excitation on the real system, for a specific sampling period. The resulting mathematical model is used to design and simulate a continuous and discrete PID controller, Mamdani and Sugeno fuzzy logic controllers, as well as ANFIS based fuzzy logic controller. The results of the applied controllers are analyzed and compared, based on the output overshoot, the rise and settling time. It can be concluded that we got best results (least settling time and the least overshoot) when fuzzy logic controller with ANFIS was used, while in terms of speed and rise time, the best results were obtained when discrete PID control algorithm was used.
Keywords: Heliostat, least-square, PID, fuzzy logic conrol, Adaptive Neuro-Fuzzy Inference System (ANFIS)